1998
DOI: 10.1203/00006450-199811000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Height Associated with a Translation Start Site Polymorphism in the Vitamin D Receptor Gene1

Abstract: The function of 1,25-dihydroxyvitamin D3 in bone development is to regulate the differentiation or proliferation of osteoblastic, osteoclastic, and chondrocytic lineage, affecting bone mineralization and linear bone growth. An A(T/C)G substitution exists in the first of the two putative translation initiation sites in exon 2 of the vitamin D receptor (VDR) gene. We studied the relationship between exon 2 polymorphism and height in 90 healthy Japanese female subjects aged 18-20 y, who had attained final height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
3
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
2
28
3
9
Order By: Relevance
“…Taq1 gene polymorphism genotypes frequencies differ among different ethnicities, different cancer types (Bid et al, 2005), and methodology by which Taq1 VDR polymorphism was investigated, sample size and vitamin D serum levels (Onen et al, 2008). Among Indian individuals the frequencies of Taq1 variants were 49%, 43% and 8% (Bhanushali et al, 2010) while Japanese study showed 77%, 22% and 1% (Minamitani et al, 1998) and a Turkish, study showed frequency of 40.8%, 47.9% and 11.2% (Dilmec et al, 2009) for TT, Tt and tt respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Taq1 gene polymorphism genotypes frequencies differ among different ethnicities, different cancer types (Bid et al, 2005), and methodology by which Taq1 VDR polymorphism was investigated, sample size and vitamin D serum levels (Onen et al, 2008). Among Indian individuals the frequencies of Taq1 variants were 49%, 43% and 8% (Bhanushali et al, 2010) while Japanese study showed 77%, 22% and 1% (Minamitani et al, 1998) and a Turkish, study showed frequency of 40.8%, 47.9% and 11.2% (Dilmec et al, 2009) for TT, Tt and tt respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, such as improved nutrition, have led to a progressive increase in height, but the genetic contribution to height is still remarkable, and variations in a number of genes have been associated with height: DRD2, which encodes the dopamine D2 receptor [31]; VDR, which encodes the vitamin D receptor [32]; COL1A1, which encodes the α1-chain of type I collagen [33]; ESR1, which encodes the α-chain of the oestrogen receptor [34]; and LHB, which encodes the luteinizing hormone beta polypeptide [35].…”
Section: Haplotypesmentioning
confidence: 99%
“…DNA was prepared from archival frozen material using conventional techniques (SDS lysis, proteinase K digestion, phenol/chloroform extraction and ethanol precipitation). PCR for the relevant regions of the VDR gene and restriction enzyme digestion of the products were done essentially as described for the FokI, 1 BsmI, 2 ApaI 3 and TaqI. 3 RFLPs.…”
Section: Vdr Genotypingmentioning
confidence: 99%
“…3,4,7 Reduced bone loss associated with liver transplantation is less frequent in transplant patients who possess the BsmI and ApaI aa and bb genotypes for VDR. 8 Polymorphism at the ATG initiation codon (FokI site) has been associated with genetic determination of final height in Japanese subjects, with heterozygotes at this locus achieving a greater final height than homozygotes for either allele, 1 and with heritable variation in bone mineral density. 9 Polymorphism at both the FokI and TaqI sites has been associated with variation in intervertebral disc degeneration in males.…”
mentioning
confidence: 99%